2008
DOI: 10.1002/asia.200700372
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Structure of Monomeric, Trimeric, and Mixed Phenylcyanamides

Abstract: In a new synthetic approach phenylcyanamide (Hpca) was synthesized by methylation of phenylthiourea followed by a basic work-up. All products along the synthetic route have been fully characterized by means of NMR, IR, and X-ray studies. The first structural report of neutral mixed crystals of phenylcyanamide containing monomeric and trimeric Hpca is presented. Examination of these intriguing mixed crystals revealed the formation of distinct layers of monomeric and trimeric Hpca. These layers are interconnecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 62 publications
0
5
0
1
Order By: Relevance
“…Although phenylformylcyanoamide is neither hygroscopic nor air sensitive, it should be stored under inert gas since it slowly decomposes in the presence of moisture according to Equation (10). The labile phenylcyanoamide reacts further to give the trimer 53 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Although phenylformylcyanoamide is neither hygroscopic nor air sensitive, it should be stored under inert gas since it slowly decomposes in the presence of moisture according to Equation (10). The labile phenylcyanoamide reacts further to give the trimer 53 …”
Section: Resultsmentioning
confidence: 99%
“…Köhler and Jäger were the first who addressed explicitly the carbodiimide/dicyanoamide problem as they studied phenyldicyanoamide and phenylcyanocarbodiimide 63. We prepared phenyldicyanoamide in a slightly modified synthetic procedure from potassium phenylcyanoamide53 and cyanogen bromide in acetonitrile (Scheme ) and recrystallized from chloroform.…”
Section: Resultsmentioning
confidence: 99%
“…[4a] In the last decade, this trimerization process leading to promising melaminate salts has been of great interest to several groups. [4][5][6] In addition, the synthesis and structural investigations of a series of hitherto unknown dicyanoamide salts (alkaline earth metal, [7] ammonium, [8] guanidinium, [9] rare earth metals, [10] and guanylurea [11] ) have been reported recently. Schnick et al showed that trimerization of Na[N(CN) 2 ] (NaA C H T U N G T R E N N U N G [dca]) irreversibly occurs above 380 8C.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, Madelung and Kern observed the trimerization of sodium dicyanoamide Na[N(CN) 2 ] at “dark red heat” and isolated the trimerization product sodium melaminate Na 3 [C 3 N 6 (CN) 3 ] after recrystallization from water (Scheme ) 4a. In the last decade, this trimerization process leading to promising melaminate salts has been of great interest to several groups 4–6. In addition, the synthesis and structural investigations of a series of hitherto unknown dicyanoamide salts (alkaline earth metal,7 ammonium, [8] guanidinium,9 rare earth metals,10 and guanylurea11) have been reported recently.…”
Section: Introductionmentioning
confidence: 99%
“…die Schwingungsdaten von einem angenommenen [Si{NCCr(CO) 5 } 6 ] 2− ‐Komplexion mit einem Si(NC) 6 ‐Kern beschrieben . Unserem Interesse an der Pseudohalogenchemie (insbesondere an Cyanid/Halogenid‐Austauschreaktionen) folgend, möchten wir hier über die Synthese von Salzen mit [SiF(CN) 5 ] 2− ‐ und [Si(CN) 6 ] 2− ‐Dianionen berichten und damit diese Lücke in der Hauptgruppenchemie schließen.…”
Section: Figureunclassified